Safety and efficacy of itepekimab in patients with moderate-to-severe COPD: a genetic association study and randomised, double-blind, phase 2a trial. Issue 11 (November 2021) - Rabe, Klaus F; Celli, Bartolome R; Wechsler, Michael E; Abdulai, Raolat M; Luo, Xiaodong; Boomsma, Maarten M; Staudinger, Heribert; Horowitz, Julie E; Baras, Aris; Ferreira, Manuel A; Ruddy, Marcella K; Nivens, Michael C; et al.
Summary: Background: Genetic data implicate IL-33 in asthma susceptibility. Itepekimab, a monoclonal antibody targeting IL-33, demonstrated clinical activity in asthma, with potential in chronic obstructive pulmonary disease (COPD). In this study we first aimed to test the hypothesis that genetic variants in the IL-33 pathway were also associated with COPD. On the basis of the strong association of IL-33 pathway genes with pulmonary diseases like asthma and COPD, we conducted this phase 2a trial to assess the safety and efficacy of itepekimab in patients with moderate-to-severe COPD on a stable regimen of triple-inhaled or double-inhaled background maintenance therapy. Methods: In this two-part study, genetic analyses of loss-of-function and gain-of-function variants in the IL-33 pathway, previously associated with asthma risk, were initially characterised for COPD. We then did a double-blind, phase 2a trial comparing itepekimab with placebo in patients with moderate-to-severe COPD despite standard therapy, at 83 study sites in ten countries. Patients aged 40–75 years who were current or former smokers, had been diagnosed with COPD for at least 1 year, and were on a stable regimen of triple-inhaled or double-inhaled background maintenance therapy, were randomly assigned (1:1) to receive itepekimab 300 mg or placebo, administered as two subcutaneous injections every 2 weeks for 24–52 weeks. The primary endpoint of the phase 2a trial was annualised rate of moderate-to-severe acute exacerbations of COPD during the treatment period. The key secondary outcome was change in prebronchodilator FEV1 from baseline to weeks 16–24. Prespecified subgroup analyses were done for each of the endpoints, including by smoking status. Efficacy and safety analyses were done in all participants who received at least one dose of assigned treatment (modified intention-to-treat population). This trial is registered at ClinicalTrials.gov (NCT03546907 ). Findings: Genetic analyses demonstrated association of loss of function in IL33 with reduced COPD risk, and gain of function in IL33 and IL1RL1 variants with increased risk. Subsequent to this, in the phase 2 trial, 343 patients were randomly assigned to placebo (n=171) or itepekimab (n=172) from July 16, 2018, to Feb 19, 2020. Annualised rates of acute exacerbations of COPD were 1·61 (95% CI 1·32–1·97) in the placebo group and 1·30 (1·05–1·61) in the itepekimab group (relative risk [RR] 0·81 [95% CI 0·61–1·07], p=0·13), and least squares mean prebronchodilator FEV1 change from baseline to weeks 16–24 was 0·0 L (SD 0·02) and 0·06 L (0·02; difference 0·06 L [95% CI 0·01–0·10], p=0·024). When analysis was restricted to former smokers, treatment with itepekimab was associated with nominally significant reductions in acute exacerbations of COPD (RR 0·58 [95% CI 0·39–0·85], p=0·0061) and FEV1 improvement (least squares mean difference 0·09 L [0·02–0·15], p=0·0076) compared with placebo. Current smokers treated with itepekimab showed no treatment benefit versus placebo for exacerbations (RR 1·09 [0·74–1·61], p=0·65) or FEV1 (least squares mean difference 0·02 [−0·05 to 0·09], p=0·54). Treatment-emergent adverse events (TEAEs) occurred in 135 (78%) patients in the itepekimab group and 136 (80%) in the placebo group. The most common TEAEs were nasopharyngitis (28 [16%] in the itepekimab group vs 29 [17%] in the placebo group), bronchitis (18 [10%] vs 14 [8%]), headache (14 [8%] vs 23 [13%]), and upper respiratory tract infection (13 [8%] vs 15 [9%]). Interpretation: The primary endpoint in the overall population was not met, subgroup analysis showed that itepekimab reduced exacerbation rate and improved lung function in former smokers with COPD. Two phase 3 clinical studies are ongoing to confirm the efficacy and safety profile of itepekimab in former smokers with COPD. Funding: Sanofi and Regeneron Pharmaceuticals.